A genome-wide association study of non-HPV-related head and neck squamous cell carcinoma identifies prognostic genetic sequence variants in the MAP-kinase and hormone pathways. (June 2016) - Azad, Abul Kalam; Bairati, Isabelle; Qiu, Xin; Girgis, Hala; Cheng, Lu; Waggott, Daryl; Cheng, Dangxiao; Mirshams, Maryam; Ho, James; Fortin, André; Vigneault, Eric; Huang, Shao-Hui; et al.
Highlights: GSVs in the MAP-Kinase and estrogen pathways were associated with OS in HNC patients. ESRRG variant is a potential splicing site disruptor sequence at the transcript level. Higher protein expression of ESRRG and CACNA2D1 is associated with poor OS. Abstract: Background: Carcinomas of the oral cavity, pharynx and larynx are referred to as head and neck cancers (HNC); together they account for 2–3% of all newly diagnosed cancers in North America. Between 40–50% of HNC are early diagnosed at stages I–II. The 5-year and 10-year relative survival rates are 61% and 50%, respectively. Germline genetic sequence variants (GSV) have become increasingly found to have prognostic implications in a variety of cancers. Identifying these variants may have important clinical and biological implications. Methods: We conducted a genome-wide association study (GWAS) in 531 Stage I–II radiation-treated HNC patients (originally recruited for α-tocopherol/β-carotene placebo-controlled secondary prevention study) and used a replication cohort of 566 HNC patients of all stages, of mostly non-HPV-related cancers. Survival rates were estimated by the Kaplan-Meier method. Cox proportional hazards models adjusted for potential clinical factors and principal components were used to test for associations between the GSV and overall survival (OS) in these tumors. Results: The median follow-up time for OS was 9.21 years (GWAS cohort) and 2.37 years (replication cohort). In both cohorts, CACNA2D1 :rs2299187, ESRRG :rs946465 and ESRRG: rs1416612 were each individually significantly associated with survival. In silico analysis of ESRRG :rs946465 identifies that it produces a splice variant in ESRRG. Variant alleles of CACNA2D1 :rs2299187 and ESRRG: rs946465 were associated with higher expression of the corresponding protein. Conclusions: Putatively functional polymorphisms in the MAP-Kinase and estrogen pathways, identified through GWAS and replicated in an independent dataset were associated with the survival of HNC patients.